Pengaruh Work From Home terhadap Job Satisfaction yang Dimediasi Work Life Balance dan Dampaknya terhadap Employee Performance Industri Perbankan di Jakarta - Siti Wahyuni; Justine Tanuwijaya; Aisyah Gayatri; Adam Maulana; Ismail Hakki Mirici (Universitas Jember, 2024)
This study aimed to analyze the effect of work from home on job satisfaction mediated by work life balance and its impact on employee performance in the banking industry in Jakarta with the variables work from home, job satisfaction, and organizational identification as independent variables and employee performance as the dependent variable, work life balance as a mediating variable. The method used in sampling in this study was purposive sampling with a total of 200 employees as respondents. Hypothesis testing using the AMOS analysis tool. The results of testing the hypothesis in this study show that work from home has a positive effect on work life balance, work from home has a positive effect on job satisfaction, work life balance has a positive effect on job satisfaction, there is a work from home effect on job satisfaction which mediated by work life balance, job satisfaction has a positive effect on organizational identification, and organizational identification has a positive effect on employee performance. Keywords: Work From Home, Work Life Balance, Job Satisfaction and Organizational Identification, Employee Performance